Наслідки вступу України до СОТ у контексті використання її експортного потенціалу - Нагірна, В.П. (Український географічний журнал, 2011)
Из общественно-географических позиций дана оценка эффективности использования экспортного потенциала Украины в связи с вступлением ее в ВТО. Подведены итоги членства Украины в ВТО за 2008 – 2010 гг., дан анализ его влияния на экономику страны, выявлены положительные и отрицательные стороны. Обозначены обязательства Украины в связи с членством в ВТО. Раскрыта товарная и географическая структуры экспорта, определены основные отрасли, формирующие экспортный потенциал страны. Акцентировано внимание на преобладании сырьевой ориентации товаров, экспортируемых из Украины. Выявлены особенности импорта товаров после вступления в ВТО. Сформулированы перспективные направления эффективного использования экспортного потенциала страны в разрезе основных товарных групп. From the human-geographical positions it is given an assessment of effectiveness of Ukraine’s export potential using in connection with its entry into WTO. The results of Ukraine’s participation in WTO during 2008-2010 are summarized, its influence on the economy of the country, positive and negative aspects are analyzed. Ukraine’s commitments connected with its participation in WTO are described. The commodity composition and geographical structure of the export are characterized, the main branches, which form export potential of the country, are defined. It is emphasized on predominance of raw materials in Ukraine’s export. The features of merchandise imports after Ukraine’s entry into WTO are shown. The long-term directions of effective using of the country’s export potential for main commodity groups are grounded.